Purification of cinnamic acid and aporphine alkaloids from enicosanthellum pulchrum twig extract and their biological activities - Nordin N.; Yazid N.S.M.; Zajmi A.; Elias M.H. (Bentham Science Publishers B.V., 2024)
Indexed by WOS/SCOPUS